Ethnic conflict and economic disparity: Serbians and Albanians in Kosovo - Sumon Kumar Bhaumik; Ira N. Gang; Myeong-Su Yun (Rutgers University, Department of Economics, 2006)
Using the Living Standards Measurement Study (LSMS) household survey from post-conflict Kosovo we investigate the comparative economic well-being of Serbs and Albanians. An Oaxaca decomposition shows Serb households are both better endowed with income generating characteristics, such as education, and receive higher returns to these characteristics than Albanian households. Despite these advantages, Serb households have lower living standards, on average, than Albanian households. Most of the difference in living standards between Serb and Albanian households is on account of unobserved non-economic factors. This has serious implications for the political economy of policymaking in post-conflict Kosovo.
Keywords: I32; O12; J15; 330; Poverty; ethnicity; transition; consumption